Synergistic activity of friedelan-3β-ol isolated from Euphorbia lactea and doxorubicin against MDA-MB-231 breast cancer cell line - Pengnam, Supusson; Wongprayoon, Pawaris; Limpachayaporn, Panupun; Rayanil, Kanok-on; Charoensuksai, Purin (Science, Engineering and Health Studies, 2022)
The cytotoxic activity of three triterpenoid compounds namely, friedelin [1], friedelan-3β-ol [2] and taraxerol [3] isolated from hexane fraction Euphorbia lactea Haw. was investigated in breast cancer cell lines MDA-MB-231 and MCF-7. Dose-dependent cytotoxic activity of these compounds was detected in MDA-MB-231 cells. Of the three compounds, [2] elicited the strongest inhibitory effect. The interplay between [2] and doxorubicin (Dox) in a series of combination treatments was analyzed in MDA-MB-231. Computer modeling software CompuSyn revealed that [2] and Dox exhibited a synergistic relationship over a broad range of concentration. The ratio of [2]:Dox at 25:1 µg/mL was predicted to achieve a 90% inhibitory effect with the lowest dose of each agent, thus allowing a dose reduction of [2] and Dox by 30 and 3 fold, respectively. Finally, the percentage of apoptotic cells in MDA-MB-231 treated with [2]:Dox at a 25:1 µg/mL combination was markedly higher than cells treated with 1x and 2x the concentration of each individual agent, supporting the predicted synergism. Together, the results highlighted [2] as an anticancer phytochemical exhibiting synergistic activity with Dox and warranted further research to assess the possibility to exploit this synergy for breast cancer treatment.